Epilepsy in Children with Cerebral Palsy - Kaźmierkiewicz, Kornelia; Chojnacka, Martyna; Spychalska, Weronika; Piotrowicz, Emilia (Quality in Sport, 2025)
Introduction and aim of the study: Epilepsy is one of the most common disorders in children with cerebral palsy. In addition, due to the variety of symptoms and the possibility of co-occurrence with other disorders, it is often difficult to diagnose. This article presents the epidemiology, pathophysiology, seizure classification, diagnosis, and treatment of epilepsy in patients with CP. In addition, the psychosocial aspect of epilepsy is taken into account and the issue of SUDEP, or sudden unexpected death associated with epilepsy, is presented. The purpose of the study is to show an overview of the current state of knowledge about epilepsy in children with CP. Materials and methods: The paper analyzes studies in databases such as PubMed, Google Scholar, ResearchGate, and other scientific databases. Clinical studies, preclinical studies, and review papers on the incidence of epilepsy in children with cerebral palsy were searched. Conclusions: Epilepsy in children with CP is a challenging and important clinical problem. Effective diagnosis, appropriate selection of medications, and subsequent monitoring of treatment are important. In addition, to improve the quality of life and functioning of patients, it is worthwhile to educate parents and caregivers, as well as provide psychological care. In the treatment of children with CP and epilepsy, the cooperation of many specialists such as neurologists, physiotherapists, occupational therapists, and psychologists is crucial. Further research is needed not only on pathophysiology but also on new therapeutic solutions, which will contribute to an even more individualized approach to patients with CP and epilepsy.